Are the functional movement analysis scores of handball players related to athletic parameters? - Atalay, E. S.; Tarakci, D.; Algun, C. (Journal of Exercise Rehabilitation, 2018)
Handball is a popular sport in many countries. There is lack of knowledge about handball athlete`s functional movement capacity. The aim of this study is to investigate the Functional Movement Screen (FMS) scores, to evaluate the injury risks of handball athletes and to determine its relationship with athletic performance. A total of 51 professional handball players were included in this study. The sport-specific features and demographic data were recorded. The functional movement analysis was performed, agility and balance and force were evaluated. 37 were females and 14 were males. The mean age 21.00±4.50 years (range, 16-35 years). The mean FMS scores of handball athletes were 12.86±2.57. In addition, asymmetries were found between the left and right side FMS scores. There was a statistically significant poor correlation between the FMS and agility (r=0.292, P=0.038) and balance (right: r=0.224, P=0.024; left: r=0.228, P=0.022). Handball is a risky sport for injuries; therefore, athletes, coaches, and medical staff should recognize about the removal of functional deficiency before performance training. The FMS is a useful and cost-effective approach to identify these deficiencies. It is necessary not only to prevent injuries, but also to improve performance. These tests must be done before every season and, then, corrective, medical, or conservative approaches may be applied to athletes before performance training. (Clinical Trial ID: NCT03468569)